828 STITCH And B**** - A Novel Programme Combining Pastoral Support and Surgical Skills. (12th October 2021) - Lochab, S; Stanier, P; Rooker, J
Abstract: Aim: Foundation training can be a challenging time for Junior doctors; though help and support is offered, it is not always taken up. This programme aims to create a safe environment to facilitate discussion and provide pastoral support alongside teaching them new surgical skills. Method: Four different sessions were organised over the period of four months (August 2020 – November 2020) and FY1/FY2 doctors working in the Orthopaedic department at the GWH, Swindon were invited to attend. Each session focussed on assorted suturing techniques and knot tying. In addition, the facilitator directed conversation towards opportunities to discuss frustrations, challenges, queries as well as positive occurrences. A questionnaire was distributed at the final session to evaluate participant experience. Results: 100% of attendees agreed or strongly agreed that they found their FY1 rotation challenging so far. 100% also scored 9/10 when asked how comfortable they were talking about concerns, worries or issues at these sessions. All the participants recorded 'yes' when asked if the session provided them with a listening ear, helpful advice, feeling supported, understanding/empathy and reassurance. 100% of the attendees scored that their confidence at suturing had improved (average: 4 points on a scale of 1-10). Conclusions: Through these sessions, practical changes and improvements were achieved in the running of the Trauma and Orthopaedic department. Placement feedback was obtained, suggestions on things to improve or change and key issues were escalated to supervisors. There do not appear to be any similar programmes run that combine directed pastoral support and surgical skills teaching.